Physiological and biochemical mechanisms of the hen’s body recovery from dermanyssosis associated with deacarization - E. N. Indyuhova; M. V. Arisov; V. I. Maximov; T. O. Azarnova (Российский паразитологический журнал, 2021)
The purpose of the research is to study the efficacy of the insectoacaricide "5% D-cyphenotrine emulsion" against infestation of birds with Dermanyssus gallinae (dermanyssosis) after the deacarization of the poultry building and to characterize physiological and biochemical mechanisms of the recovery of Hy-Line hens after removed parasites.Materials and methods. A parasitological examination of the poultry farm found D. gallinae in one of the poultry buildings. Given positive results of the drug efficacy against the poultry red mite, we analyzed the morpho-physiological and physiological and biochemical parameters of the hen’s blood before and 10 and 20 days after the treatments. Changes in the ethological status of birds were recorded. We used 0.005% aqueous emulsion of "5% D-cyphenothrin emulsion" for treatment. To obtain it, the drug was diluted with water at a ratio of 1:1000 immediately before use.Results and discussion. After double treatment with "5% D-cyphenotrine emulsion" of the shop with hens from the test group, no live poultry red mite was found. Within 20 days after the disease reduction, representatives of this group showed high concentrations of cortisol which were 2.3–2.4 times (p < 0.001) higher than those of healthy hens. This indicates that the stress state of hens still remains after the parasitizing of D. gallinae. In addition, the recovery process takes a long time and with great stress for all systems of their body. This is also confirmed by a high level of lipid peroxidation. At the same time, high intensity of gluconeogenesis and, as a result, deterioration of lipid and protein metabolism were recorded in the hens in question. The positive results indicate an increasing need for additional energy expenditures which are paramount for the effective and well-timed implementation of adaptation mechanisms. It should be noted here that the values of all the above-mentioned indicators tend to normalize by the end of the study period. The changes noted in the blood of birds indicate the restoration of a number of body systems. The poultry red mite as an emergency factor affects the morphophysiology of the blood, in particular, the level of white blood cells, which is restored by the 10th day after deacarization, which triggers regenerative and reparative processes. There were also changes in the number of cells of the immune system, an increase in hemoglobin concentration to control values and optimization of behavior in representatives of the test group which are largely related to the normalized physiological activity of the thyroid gland after the poultry building deacarization. We found a partial recovery of the hen’s body systems after the poultry building deacarization with the drug "5% D-cyphenotrine emulsion", which is due to the long-term parasitizing of D. gallinae, a stressor of extreme strength.